Molecular identification of microorganisms in agriculture, ornamental and forest crops in Costa Rica, 2009-2018. Part 2 - Blanco-Meneses, Mónica (2024)
Introduction. The identification and detection of microorganisms using molecular techniques has become a very helpful tool for the disease diagnosis and organisms present in crops. Pathogenic, non-pathogenic organisms, biological controllers and other microorganisms used as competitors, antagonists or mutualists can be isolated from agriculture, ornamental and forest crops. Objective. To identify the taxonomic level, by molecular techniques, pathogenic and non-pathogenic bacteria and yeast isolated in agriculture, ornamental and forest crops in Costa Rica, and preserve the material in a DNA bank. Materials and methods. Between 2009 and 2018, the Molecular Techniques Laboratory at the Plant Protection Research Center, Universidad de Costa Rica, received a total of 181 isolates of bacteria and yeast for detection by end-time and real-time PCR and identification through sequencing of specific regions. Results. Of the total samples, 94.2 % were analyzed by sequencing and 5.8 % by PCR. Using PCR, bacteria species were identified in rice, such as Burkholderia spp., Acidovorax avenae and Pseudomonas fuscovaginae. Through sequencing of the partial 16S region, 172 samples of bacterial species were identified, and five samples of yeast species with the ITS region of the 18S ribosomal RNA. Microorganisms isolated from eighteen species of agricultural, ornamental and forest plants were identified. The genera most identified were Pseudomonas, Bacillus and Enterobacter, and in the case of yeast, Candida, Pichia, and Wickerhamomyces. Conclusion. This research allowed the taxonomic identification of bacteria and yeast from crops in Costa Rica. In addition, a consultation input was developed, along with the possibility of future use of the microorganisms that are preserved at the DNA bank.